(untitled) (Research, Society and Development, 2020)
The performance of work activities with inadequate ergonomic execution and for a prolonged period can cause muscle damage of different severities in workers, both in rural and industrial areas. With this in mind, we aim to analyze the scientific evidence available in the literature on ergonomics and musculoskeletal disorders in workers in this integrated literature review. From a methodological point of view, this study is an integrative literature review, developed in seven stages: formulation of the guiding question; development of inclusion and exclusion criteria; location and selection of studies; critical evaluation of studies; data collection and analysis; presentation and interpretation of results, and finally presentation of the review. Regarding the results, it was noticed that most studies addressed the presence or possible development of Work-Related Musculoskeletal Disorders. Which are injuries to the muscles, tendons, ligaments, joints and nerves and which are related to the activities performed in the work environment. Among these activities, the development of tasks using inadequate posture, load extremes, work overload, little rest time and repetitive effort are highlighted. It is concluded that professionals who need a lot of physical effort in their work environment and who perform activities with inadequate ergonomics have a high probability for the development of musculoskeletal changes. It is necessary that there is continuity in research related to muscle disorders in workers, as well as the implementation of interventions that minimize the ergonomic errors adopted by professionals.